1975
DOI: 10.1002/1097-0142(197510)36:4<1250::aid-cncr2820360410>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatocellular carcinoma with adriamycin.Preliminary communication

Abstract: In a Phase I1 clinical trial, 14 patients with histologically proven primary hepatocellular carcinoma were treated with adriamycin administered intravenously a t a dose of 75 mg/mz every 3 weeks. All 11 evaluable p a t i w t s responded with 3 exhibiting complete tumor regression after two, three, and five courses of adriamycin respectively. The remissipn durations for these 3 were 3, 6, and 7 months, a n d their survivals were 8, 9, and I3 months, respectively. The median survival of the evaluable patients is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(51 citation statements)
references
References 10 publications
1
49
0
1
Order By: Relevance
“…including three complete responses in advanced HCC ( Table 1) (8). However, subsequent studies demonstrated only limited efficacy (<20% clinical responses) without significant survival benefit (9)(10)(11)(12)22).…”
Section: Introductionmentioning
confidence: 99%
“…including three complete responses in advanced HCC ( Table 1) (8). However, subsequent studies demonstrated only limited efficacy (<20% clinical responses) without significant survival benefit (9)(10)(11)(12)22).…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda earlier studies on PHC before the HIV epidemic showed high prevalence rates of HBV (60-80%) among patients with PHC [4][5][6][7] . Indeed analysis from Kampala cancer registry indicated an increase of PHC among women over the periods 1960-1980 and 1991 to 2005.…”
Section: Introductionmentioning
confidence: 99%
“…42 might be explained by the following: 1) superselective intra-hepatic arterial injection of a relatively large dose of an anticancer drug was made, 2) cirrhosis of the liver was absent and impairment of liver function was very slight, 3) the tumor was localized and encapsulated-a relatively benign nature of the encapsulated HCC has recently been e m p h a s i~e d ,~~.~* 4) the tumor was hypervascular making the intraarterially administered chemotherapeutic agent more effective, 5) the tumor cells were already necrotic in places and not very viable from the beginning, and 6) there was no metastasis intrahepatically and extrahepatically. T o our knowledge, there has as yet been not a single record of complete necrotization of HCC with chemotherapy alone, although occasional cases of remarkable response to chemotherapy have appeared in the literatu re .26, 28 The cause of fatal renal failure was most probably disseminated intravascular coagulation as suggested by the marked reduction in platelet count, mild unconjugated hyperbilirubinemia, and poikilocytosis which were not seen while he was in the hospital. The histological findings of the kidney were compatible with the diagnosis of intravascular hemolysis.…”
Section: Discussionmentioning
confidence: 99%